The effect of creatine monohydrate loading on cognitive performance, mood, sleepiness, and perceived workload following sleep restriction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Janvresse, Juliette Victoire Constance (Massey University, 2023)
Background: Sleep restriction (SR; i.e. not getting enough sleep per 24 hours for one or multiple nights) impairs cognitive performance and mood, which can compromise capability and safety. SR-related performance deficits may be underpinned by disruptions to brain energy metabolism. Sleep loss appears to reduce brain phosphorylcreatine (PCr; also called creatine phosphate and phosphocreatine), which supports the regeneration of adenosine triphosphate (ATP) from adenosine diphosphate (ADP). Since creatine supplementation increases tissue PCr, including in the brain, it may mitigate possible SR-related cognitive impairments. Aim: To assess the effect of a 7-day creatine monohydrate (CrM) loading protocol on cognitive performance, mood, subjective sleepiness, and perceived workload following one night of SR (3 hours time-in-bed; TIB). Methods: A double-blinded, randomised, placebo-controlled cross-over trial was conducted with 7 healthy participants (3 men and 4 women); age, 28.0 ± 4.6 years (range, 22-35 years). Participants ingested 20 g∙dayˉ¹ of CrM or placebo (i.e. tapioca) divided into 4 equal 5 g doses for 7 days followed by a single SR night (3 hours TIB). Cognitive performance (10-minute Psychomotor Vigilance Task; PVT), mood (fatigue and vigour), subjective sleepiness, and perceived workload were measured following ~8 hours of sleep prior to creatine supplementation and following the creatine loading protocol and SR. A minimum of a 5-week wash-out period separated the two trial arms. Linear mixed effects models were employed to analyse data. Results: SR slowed mean reciprocal reaction time (p = 0.01) and mean 10% fastest reaction time (p = 0.02), increased fatigue (p = 0.004), subjective sleepiness (p = 0.009), workload (p = 0.02), and reduced vigour (p <0.001); however, it did not alter the number of lapses (p = 0.60) and mean 10% slowest reaction time (p = 0.60). CrM loading had no effect on cognitive performance, mood, subjective sleepiness, or workload. Conclusion: A single night of SR (3 hours TIB) negatively affected aspects of PVT performance, mood, subjective sleepiness, and perceived workload; however, CrM loading (20 g∙dayˉ¹ for 7 days) did not appear to mitigate the effects of SR.
Keywords: sleep loss; psychomotor vigilance task; randomised cross-over trial; 321004 Nutritional science